An Analysis of Social Media Usage Levels among Students at School of Physical Education and Sport in Some Variables - Dinçer, Nevzat; Kilinç, Zühal (Asian Journal of Education and Training, 2019)
The purpose of the research was to analyze the social media usage levels of the students at School of Physical Education and Sport in Batman University in terms of some variables. The research group consisted of total 262 students including 164 female students and 98 male students who have studied at School of Physical Education and Sport in Batman University during the spring term of the academic year 2017-2018 and participated in the research voluntarily. The research data were collected with “The Scale of Social Media Usage Level” developed by Toraman (2013). The scale is a five-point likert scale with 19 statements and one dimension. In estimation of total points from the social media usage level scale, the values were registered as “19-44” Elementary Level, “45-70” Medium Level, and “71-95” Advanced Level presented by Toraman (2013). As a result of the research, it was clear that the social media usage levels of the students at School of Physical Education and Sport were at medium levels, there were not significant differences between the students’ gender, social media usage reasons and social media usage levels, there were significant differences between the students’ social media usage duration, social media subscription and social media usage levels.